(untitled) (Práxis Educativa, 2020)
It explores some counterpoints between the Field Education and the Common Curricular National Basis proposal. It makes an overview analysis of the Itinerant Schools Study Plan and the Curricular Guidelines of the Paraná Field Education that, as field workers achievements in the scope of educational policies, guide the realization of the pedagogical practices in the field schools. In this process counterbalance, the National Basis, translated in the Paraná Curricular Referential, points out its class-based and market character, when considered the bonds of its authors with the dominant Brazilian class entities. Its proposal prioritizes the census assessments, reinforcing some subjects in detriment of others, attaching far less importance and discarding the specificities, the diversity and the wide access to knowledge, elements that underlie the Field Education proposition. Keywords: Field Education. Curricular Guidelines. Common Curricular National Basis.